APLIKASI OBAT HERBAL DAN MANAJEMEN KESEHATAN IKAN BAGI PETANI DI DESA PASIE PINANG KECAMATAN MEUREUBO KABUPATEN ACEH BARAT - Rinawati Rinawati; Zulfadhli Zulfadhli; Radhi Fadhillah (Jurnal Marine Kreatif, 2020)
Disease infection in fish farming causes a decrease in production yields and crop failure. On the other hand, the decline in production and crop failure is also due to the lack of knowledge and skills of farmers in prevention and treatment. Treatment using chemical drugs continuously causes resistant fungi / bacteria so that it is difficult to eradicate. The solution offered to solve partner problems is to provide information on fish health management and the use of natural medicine. Implementation stages include: program preparation, program implementation, monitoring and evaluation, workshops and reporting. The results of this service show that fish farmers get increased knowledge about fish health management and the use of herbal medicine.